2018
DOI: 10.1103/physrevd.97.095033
|View full text |Cite
|
Sign up to set email alerts
|

Searching for confining hidden valleys at LHCb, ATLAS, and CMS

Abstract: We explore strategies for probing hidden valley scenarios exhibiting confinement. Such scenarios lead to a moderate multiplicity of light hidden hadrons for generic showering and hadronization similar to QCD. Their decays are typically soft and displaced, making them challenging to probe with traditional LHC searches. We show that the low trigger requirements and excellent track and vertex reconstruction at LHCb provide a favorable environment to search for such signals. We propose novel search strategies in b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 43 publications
1
86
0
Order By: Relevance
“…Searches for dark showers can be complemented by searching for decays of individual dark pions decaying in the LHC detectors, in particular at LHCb with its low trigger thresholds and accurate particle reconstruction. Some work in this direction has recently been published [71,72], and we expect that similar studies can also constrain our flavoured dark sector scenario.…”
Section: Summary Of Constraints and Conclusionmentioning
confidence: 57%
“…Searches for dark showers can be complemented by searching for decays of individual dark pions decaying in the LHC detectors, in particular at LHCb with its low trigger thresholds and accurate particle reconstruction. Some work in this direction has recently been published [71,72], and we expect that similar studies can also constrain our flavoured dark sector scenario.…”
Section: Summary Of Constraints and Conclusionmentioning
confidence: 57%
“…Furthermore, it has been shown that the detector's vertexing and invariant mass resolution as well as its ability for particle identification makes it an excellent instrument to search for displaced muon pairs from, e.g., displaced visible decays of dark photons [44,45]. Similar searches are also sensitive to soft energy deposition from the showering and hadronization in confining hidden sectors [46,47].…”
Section: B Displaced Muons At Lhcbmentioning
confidence: 99%
“…Relatively weak interactions are sufficient for the ρ 0 decays to proceed sufficiently fast to keep the dark sector in thermal equilibrium with the SM during freeze-out, while somewhat stronger interactions allow for the dark sector to be probed with direct detection experiments and at the LHC. Rho mesons that decay promptly on collider scales as well as long-lived mesons are a generic possibility of these models, leading to a wide range of novel collider signatures, such as semi-visible jets [21][22][23] and emerging jets [16,24].…”
Section: Introductionmentioning
confidence: 99%